Stabilities and Phase Diagrams of Fast Pyrolysis Bio-oils - Li, Mingyang (Curtin University, 2020)
Fast-pyrolysis bio-oil is an important feedstock for energy application and value-added chemicals production. Phase instability of fast-pyrolysis bio-oil is a key problem taking place during bio-oil handling, storage and transport, leading to undesired severe consequences including pumping problems, blockages and combustion issues. This project reports a systematic study into the stability and phase behaviour of bio-oil and the development of a set of phase diagrams of understanding and controlling bio-oil phase stability.